HOMESTAY SEBAGAI FASILITAS PARIWISATA DARI PERSPEKTIF WISATAWAN DI KABUPATEN SAMOSIR - Mohamad Ridwan; Andi Muhammad ikhsan (Universitas Muslim Indonesia, 2019)
This research aims to know the perspective of tourists against the availability of the current homestay in Samosir. Research methods used in this research was the qualitative method with descriptive analysis techniques.In this study that will be scrutinized is the perspective of tourists against homestay Samosir Regency. Research findings: (1) the tourists prefer to stay in homestay than a hotel because of the cheaper cost.(2) the existing Services in the homestay or good already is in compliance with the expectations of tourists.(3) Yet the existence of the development of the homestay is located directly in the tourist area and there are several homestay has not been in accordance with the standard concept of homestay.